ARTYKUŁ ORYGINALNY/ORIGINAL PAPERUltrasonography, magnetic resonance imaging and conventional radiography of bone erosions in rheumatoid arthritis – a comparative study - Ciechomska, Anna; Andrysiak, Renata; Serafin-Król, Małgorzata; A. Al-Salem, Jawaher; Tłustochowicz, Witold; Zagrodzka, Magdalena; Królicki, Leszek; Jakubowski, Wiesław (Reumatologia/Rheumatology, 2005)
Objective: The presence of bone erosions in conventional radiography (CR) of the hand and foot joints is an important diagnostic criterion in rheumatoid arthritis (RA). Magnetic resonance imaging (MRI) and ultrasonography (US) have been proved to be more sensitive than CR in visualizing bone lesions in RA patients. The aim of the study was to estimate the concomitance of MRI and US findings in visualizing bone erosions, and to compare these modalities with CR. Methods: The study included 50 RA patients in a mean age 53.0±14.6 years. CR and US of both hands, and MRI of one hand were performed. The evaluated data were: the number of patients with bone erosions shown by CR, MRI and US, and the number of joints with bone erosions per patient in MRI and US. The CR, MRI and US findings were compared. Results: CR showed erosions in 32% of the examined patients while MRI in 62% and US in 68% of patients. In the patients who had no radiological bone erosions, MRI showed erosions in 44.1% and US in 50% patients. The mean number of joints with bone erosions was in MRI 2.2±2.9 and in US 2.6±3.7. The correlation between MRI and US in visualizing bone erosions was found to be very high (coefficient of correlation =0.9; p<0.005). Conclusion: MRI and US show more bone erosions in the hand joints than CR in patients with RA. The high agreement of US and MRI in showing bone erosions proves that both these methods can be applied interchangeably, depending on the availability of means and interpreters\' experience.